Bouncing back from COVID-19: a Western Australian community perspective - Sarasjärvi, Kiira Karoliina; Chivers, Paola; Bhoyroo, Ranila; Codde, Jim (Frontiers in Public Health, 2023)
Introduction: This study explored the behavioral profiles of residing Western Australians during a COVID-19 lockdown period and transitions in behavior post lockdown. Methods: A total of 313 participants (76% female, Age: M=50.1, SD=15.7 years) completed behavioral and mental health questionnaire items approximately two months after a 3-month COVID-19 lockdown in October 2020, using a retrospective recall to assess their experience during the lockdown period. Latent transition analysis (LTA) was used to identify behavioral profiles and the transitions. Indicators were identified by assessing during-post lockdown group differences (Kruskal-Wallis, Chi-square tests) and profiles described using qualitative open-ended questions. Results: Significant indicators included changes in physical activity, leisure screen time, alcohol intake, psychological distress, and loneliness, but not fast-food consumption. The significant indicators were used to form LTA models. The five latent class model showed the best model fit (Log-likelihood=-1301.66, AIC=426.12, BIC=609.68). Approximately one in four participants reported a change in their behavior profiles after the lockdown ceased. Key differences between the profiles were age, household income, education, resilience, sense of control, existing mental health issues and social relations. Washing hands and social distancing were the most recalled and effective health campaigns across the classes, with health campaigns encompassing physical activity/alcohol consumption, or domestic violence having the least attention. Discussion: Overall, while most participants recovered relatively well after the lockdown period, LTA did identify subgroups such as those who were inactive and lonely experienced more difficulties than other groups, and engagement with public health campaigns differed. The results provide important insights for future public health campaigns on how these campaigns might be diversified to effectively target more people and particular groups to maximize engagement for maintaining people’s mental health with additional focus on physical activity, alcohol consumption and domestic violence.